Molecular simulations of thermal transport across iron oxide-hydrocarbon interfaces - Carman,F; Ewen,J; Bresme,F; Wu,B; Dini,D (ACS Applied Materials and Interfaces, 2024)
The rational design of dielectric fluids for immersion cooling of batteries requires a molecular-level understanding of the heat flow across the battery casing/dielectric fluid interface. Here, we use nonequilibrium molecular dynamics (NEMD) simulations to quantify the interfacial thermal resistance (ITR) between hematite and poly-α-olefin (PAO), which are representative of the outer surface of the steel battery casing and a synthetic hydrocarbon dielectric fluid, respectively. After identifying the most suitable force fields to model the thermal properties of the individual components, we then compared different solid–liquid interaction potentials for the calculation of the ITR. These potentials resulted in a wide range of ITR values (4–21 K m2 GW–1), with stronger solid–liquid interactions leading to lower ITR. The increase in ITR is correlated with an increase in density of the fluid layer closest to the surface. Since the ITR has not been experimentally measured for the hematite/PAO interface, we validate the solid–liquid interaction potential using the work of adhesion calculated using the dry-surface method. The work of adhesion calculations from the simulations were compared to those derived from experimental contact angle measurements for PAO on steel. We find that all of the solid–liquid potentials overestimate the experimental work of adhesion. The experiments and simulations can only be reconciled by further reducing the strength of the interfacial interactions. This suggests some screening of the solid–liquid interactions, which may be due to the presence of an interfacial water layer between PAO and steel in the contact angle experiments. Using the solid–liquid interaction potential that reproduces the experimental work of adhesion, we obtain a higher ITR (33 K m2 GW–1), suggesting inefficient thermal transport. The results of this study demonstrate the potential for NEMD simulations to improve